163k views
3 votes
help with number 2 please i have no idea how to do this. it would be very helpful if you can show the steps

help with number 2 please i have no idea how to do this. it would be very helpful-example-1

2 Answers

4 votes
y = 3
y = - 2x + 3
sub in 1 y for another
3 = -2x + 3
3 - 3 = -2x
0 = -2x
0 = x....solution is (0,3)
===================
y = 3x + 2
y = -3x - 4
sub in 1 y for another
3x + 2 = -3x - 4
3x + 3x = -4 - 2
6x = -6
x = -6/6
x = -1
now sub in -1 for x in either of the original equations to find y
y = 3x + 2
y = 3(-1) + 2
y = -3 + 2
y = -1
solution is (-1,-1)

User Amreen
by
5.6k points
7 votes
Question 2 is -3

You do -2*3 which is -6 and then + 3 so it is -3
User VivekDas
by
5.9k points